2019
DOI: 10.1590/1983-21252019v32n318rc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Forest Management Practices on the Soil Macrofauna in the Arboreal Caatinga

Abstract: Forest management can lead to numerous changes of different magnitudes in the composition and diversity of soil organisms, according to the level of interference with the habitat. Within this context, this study aimed to test the influence of different types of forest management on the edaphic macrofauna community in a region of arboreal Caatinga. The study was carried out in Contendas do Sincorá National Forest, Contendas do Sincorá - Bahia. The experimental area consisted of three types of management (clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…Another factor possibly related is the high diversity and density of tree species that improved the food resources and the microclimate for soil organisms in SCS plots compared to the others, reflecting on the acceleration of the decomposition rate. This explanation corroborates which the results founded by Matos et al (2019), who evaluated the edaphic fauna in the same experimental area and in that time of the present study (1 year after forest management), observed that SCS was the management practice that most favored the abundance and diversity of the invertebrate community, mainly detritivores organisms and litter decomposers. Thus, we suggest that the SCS, as well as the lack of management condition, can be self-sustainable concerning supplying the demand for nutrients by plants since the rate of decomposition determines the efficiency of use of nutrients in forest ecosystems (Isaac and Nair 2005) Time (days) 0 1 0 0 2 0 0 3 0 0…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Another factor possibly related is the high diversity and density of tree species that improved the food resources and the microclimate for soil organisms in SCS plots compared to the others, reflecting on the acceleration of the decomposition rate. This explanation corroborates which the results founded by Matos et al (2019), who evaluated the edaphic fauna in the same experimental area and in that time of the present study (1 year after forest management), observed that SCS was the management practice that most favored the abundance and diversity of the invertebrate community, mainly detritivores organisms and litter decomposers. Thus, we suggest that the SCS, as well as the lack of management condition, can be self-sustainable concerning supplying the demand for nutrients by plants since the rate of decomposition determines the efficiency of use of nutrients in forest ecosystems (Isaac and Nair 2005) Time (days) 0 1 0 0 2 0 0 3 0 0…”
Section: Discussionsupporting
confidence: 93%
“…It may be related to changes in the vegetation structure or the entry of crop residues, which would influence the performance of the decomposing community. In agreement with this hypothesis, Barreto-Garcia et al ( 2021), Matos et al (2019) and Pereira et al (2018) found that CC, compared to SCD and SCS, was the most impactful management for the microbial activity, edaphic macrofauna, and arbuscular mycorrhizal fungi community, respectively, causing a reduction in abundance and diversity.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Além disso, Maia et al (2019) acrescentou que a sucessão de períodos de pousio contribuiu para o estabelecimento e reestruturação dos grupos de artrópodes, demonstrando a viabilidade de um ciclo de 10 anos de exploração de madeira na Caatinga analisada. Já Matos et al (2019) incrementaram afirmando que o corte seletivo por espécies se mostrou menos impactante para a macrofauna do solo, devido aos valores mais expressivos de diversidade e índice de abundância e à ocorrência de organismos mais exigentes em condições de microclima, que caracterizam áreas preservadas. Ambos autores, destacaram em suas pesquisas a importância dos insetos na detecção de mudanças ambientais na Caatinga.…”
Section: Resultsunclassified
“…Este resultado deve-se principalmente pela alta abundância de colêmbolos e formigas, e por A3 apresentar solo mais compactado que A1 e A2, criando uma condição desfavorável à ocorrência de organismos (Tabela 2). Estudos mostram a influência da quantidade e das características da vegetação na comunidade de invertebrados do solo, pois a maior quantidade e variedade de vegetação favorece maior desenvolvimento destes organismos, podendo aumentar sua abundância e riqueza (Silva et al, 2013;Marques et al, 2014, Matos et al, 2019.…”
Section: Resultados E Discussõesunclassified